Two new nematode species of the family Diplopeltidae Filipjev, 1918 (Nematoda, Araeolaimida) from coast of Vietnam - Thanh, Nguyen Vu; Hien, Nguyen Thanh; Vladimir G., Gagarin (Academia Journal of Biology, 2012)
Two new species of free-living marine nematodes from West Sea (Gulf of Siam), coast of Vietnam, were described and illustrated. Diplopeltula obesa sp. n. differs from D. indica Gerlach, 1962 by possessing shorter and thicker body, comparatively longer tail and shorter cephalic setae, Campylaimus gracilis sp. n. resemble to C. minor Timm, 1961, but differs from the later by having an another shape of amphidial fovea, another position of mouth, longer body and shorter cephalic setae.